Nanomaterials to address the genesis of antibiotic resistance in Escherichia coli - Kaushik, Mahima; Sarkar, Niloy; Singh, Amit; Kumar, Pankaj (Frontiers in Cellular and Infection Microbiology, 2023)
Escherichia is a genus of prokaryotic gram-negative bacteria which forms a vital component of the gut microbiota of homeotherms including humans. Although many members of this genus are commensals and pathogenic strains, which are responsible for some of the most common bacterial infections and can be fatal, particularly in case of newborns and children. The fecal matter in wastewater treatment plants serves as major environmental sinks for the accumulation of Escherichia. The rise in antibiotic pollution and lateral gene exchange of antibiotic-resistant genes have created antibiotic-resistant Escherichia strains or often called superbugs. The antibiotic resistance has reached a crisis level that nowadays existing antibiotics are no longer effective. One way of tackling this emerging concern is by using nanomaterials. Punitively, nanomaterials can be used by conjugating with antibodies, biomolecules and peptides to reduce antibiotic usage, whereas preventatively they can be used as either nano-antimicrobial additives or nano-photocatalytic sheets to reduce the microbial population and target superbugs of environmental Escherichia. In this review, we have explored the threat posed by pathogenic Escherichia strains in the environment, especially in the context of antibiotic-resistant strains. Along with this, we have discussed same nanomaterial mediated strategies in which the problem can be addressed by using nanomaterials as nanophotocatalytics, antimicrobial additives, drug and drug conjugates. This review also presents a brief overview of ecological threats posed by overuse of nanomaterials which warrants a balanced and judicious approach to the problem.